Predictors of prolonged vancomycin-resistant enterococci colonization in acute stroke patients admitted to an intensive care unit: A retrospective cohort study. Issue 32 (13th August 2021) - Choi, Han Eum; Lee, Jae Hyun; Sim, Young-Joo; Jeong, Ho Joong; Kim, Ghi Chan
Abstract : Abstract: To investigate the factors affecting the duration of vancomycin-resistant enterococci (VRE) colonization in stroke patients. A total of 52 stroke patients with VRE colonization were enrolled. We divided the groups into several factors and confirmed whether each factor affected VRE colonization. Independent t test, bivariate correlation analysis, and Cox proportional hazards model were used to confirm statistical significance. Among 52 patients, 28 were ischemic stroke and 24 were hemorrhagic stroke. The mean duration of the VRE colonization was 39.08 ± 44.22 days. The mean duration of VRE colonization of the ischemic stroke patients was 25.57 ± 30.23 days and the hemorrhagic stroke patients was 54.83 ± 52.75 days. The mean intensive care unit (ICU) care period was 15.23 ± 21.98 days. Independent sample t test showed the hemorrhagic stroke ( P < .05), use of antibiotics ( P < .01), oral feeding ( P < .01) were associated with duration of VRE colonization. Bivariate correlation analysis showed duration of ICU care ( P < .001) was associated with duration of VRE colonization. Cox proportional hazard model showed oral feeding ( P = .001), use of antibiotics ( P = .003), and duration of ICU care ( P = .001) as independent factors of duration of VRE colonization. Careful attention should be given to oral feeding, duration of ICU care, and use of antibiotics in stroke patients, especially hemorrhagic stroke patients, for intensive rehabilitation at the appropriate time.